2008
DOI: 10.1677/erc-07-0257
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of single nucleotide polymorphisms of FSH receptor gene suggests association with testicular cancer susceptibility

Abstract: The development of testicular germ cell tumour (TGCT) is believed to be under endocrine control but definitive proofs are lacking. Follicle stimulating hormone (FSH) levels are increased in numerous conditions associated with increased risk of TGCT and single nucleotide polymorphisms (SNPs) in the FSH receptor (FSHR) gene influence the sensitivity of the receptor to FSH. However, a possible effect of FSH on testicular carcinogenesis has never been explored. In order to analyse the possible association of FSHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 33 publications
4
32
1
1
Order By: Relevance
“…Recent evidence supports an association of TGCT with polymorphisms in these genes: we and others have reported an association with CAG/GGN repeat length of the androgen receptor gene (Giwercman et al 2004, Garolla et al 2005 and with FSH receptor gene polymorphisms (Ferlin et al 2008a), and an association with some maternal and/or offspring hormonemetabolizing genes of the cytochrome P450 family (CYP1A1, CYP1A2, CYP3A4, and CYP3A5) has been suggested (Starr et al 2005, Figueroa et al 2008.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Recent evidence supports an association of TGCT with polymorphisms in these genes: we and others have reported an association with CAG/GGN repeat length of the androgen receptor gene (Giwercman et al 2004, Garolla et al 2005 and with FSH receptor gene polymorphisms (Ferlin et al 2008a), and an association with some maternal and/or offspring hormonemetabolizing genes of the cytochrome P450 family (CYP1A1, CYP1A2, CYP3A4, and CYP3A5) has been suggested (Starr et al 2005, Figueroa et al 2008.…”
Section: Introductionsupporting
confidence: 58%
“…Associations with TGCT have been found with mutations in the androgen receptor gene (Garolla et al 2005), different lengths of the CAG and GGC repeats in exon 1 of the androgen receptor gene which modulate the sensitivity of the receptor to androgens (Giwercman et al 2004, Garolla et al 2005, polymorphisms of the FSH receptor gene which modulate FSH sensitivity (Ferlin et al 2008a), and polymorphisms in cytochrome P450 genes involved in estrogen metabolism (Starr et al 2005, Figueroa et al 2008. With regards to Endocrine-Related Cancer (2010) 17 17-25 www.endocrinology-journals.org these latter genes, an association between TGCT and CYP1A2 (rs762551), CYP3A4 (rs2740574), and CYP3A5 (rs776746) gene polymorphisms was found by one study (Starr et al 2005), whereas an association with polymorphisms in CYP1A1 (rs4886605 and rs2606345) gene was found by another one (Figueroa et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Studies dealing with genetic predisposition of TGCT frequently found differences between seminoma and nonseminoma. The gr/gr deletion of the Y chromosome is strongly associated with seminoma than with nonseminoma (Nathanson et al 2005), longer CAG repeats on the androgen receptor gene are mainly associated with nonseminoma (Giwercman et al 2004), and we also found higher association of FSH receptor (FSHR) polymorphisms only with nonseminoma (Ferlin et al 2008), and on the contrary stronger association of hydroxysteroid (17-beta) dehydrogenase 4 (HSD17B4) markers with seminoma (Ferlin et al 2010). Therefore, it might also be possible that the two classes of TGCTs might have different pathogenesis.…”
Section: Discussionmentioning
confidence: 48%
“…Most of these studies included genes involved in reproduction (Ferlin et al, 2010;Ferlin et al, 2008;Figueroa et al, 2008;Giwercman et al, 2004;Heimdal et al, 1995;Kristiansen et al, 2011;Lundin et al, 2007;Nathanson et al, 2005;Purdue et al, 2008;Rajpert-De Meyts et al, 2002;Vastermark et al, 2011). We have previously shown that the variant allele rs12014709 in the androgen receptor (AR) is significantly associated with a doubled risk for having TGCC in the same population as the current study (Vastermark et al, 2011).…”
Section: Discussionmentioning
confidence: 64%